Assessing The Effects of Irregular Migration on The Well-Being Of The Migrant Households in Delta and Edo States, Nigeria - Nwokolobia, Anthony; Ayegbunam, Ikenga Francis; Sanubi, Franklins A. (ARISTO, 2025)
This study examined the effects of irregular migration on the well-being of the migrant households in Delta and Edo States, Nigeria. A cross-sectional research design and purposive sampling technique were adopted.  Questionnaire was employed as the research instrument for this study with 716 respondents deemed usable. The theoretical and analytical framework that directs this study combines the New Economics of Labour Migration theory with the neo-classical theory, making evident their shared premise that irregular migration can be seen as a household-calculated strategy to maintain rural well-being. With the use of the Statistical Package for Social Sciences (SPSS) Version 23, the acquired data were examined using percentages, means, standard deviations, Pearson's coefficient of correlation, and linear regression analysis. The well-being of migrant households in the Delta and Edo States is positively and considerably influenced by irregular movement, according to the study. The study also showed that irregular migration improves welfare and means of subsistence, increases financial remittances, lowers family poverty, and promotes the construction of infrastructure in the home areas of migrants in the Delta and Edo States. The study came to the conclusion that, for all people, including those in the Delta and Edo States, irregular migration is an unavoidable human phenomenon in the modern day. To ensure that migrants understand the ramifications of irregular migration and the value of regular migration to the state and communities, not simply their family members, the government should actively engage migrants and maintain contact with them, rather than actively discouraging migration. The study concluded that many of the properties constructed in the neighbourhoods are owned or occupied by the immigrants and their families; it is undeniable that irregular migration has had an impact on numerous communities in the Delta and Edo States. Based on the study's findings and conclusions, the study made several recommendations, including that the governments of Delta and Edo State should appoint honourable people, notable figures, and bright academics to develop and carry out policies aimed at promoting migrants' interest in the establishment of infrastructure, including healthcare facilities, educational institutions, transportation, renewable energy, solar power, and modular refineries. In the foreseeable future, this will significantly lessen irregular migration in the Delta and Edo States.